(untitled) (Research, Society and Development, 2022)
Introduction: The COVID-19 infection caused by the coronavirus (SARS-CoV-2) has spread to become a worldwide pandemic leading to a high rate of morbidity and mortality. Physiotherapists, as professionals who work on the front lines of the pandemic, must always be aware of updates and have the skills to make decisions, detect new cases and define the appropriate treatment in the ICU. Objective: To analyze physical therapy assistance in the Intensive Care Unit for patients with COVID-19. Methods: This is a bibliographic research of the integrative literature review type, in which the Bireme and PubMed databases, and the health descriptors and mesh terms were used to elaborate the search strategy. Results: Nine studies were included in this review, studies dealing with physical therapy assistance in the ICU for patients with COVID-19. The experience of physical therapists is highlighted and they discuss the challenges and strategy for the clinical management of these patients in ICUs of different specialties, such as cardiology, neurological, pediatric and adult ICUs. Conclusion: The care provided should focus on preventing future injuries and strengthening patients in order to improve their ability to exchange gas and oxygenation. In this aspect, the physiotherapist works with the patient, seeking to carry out prevention and treatment activities, in addition to offering emotional support, as these clients, in most cases, are physically and psychologically fragile.